Implementasi Denda Pada Akad Murabahah Dalam Perspektif Ekonomi Syariah Di BMT Purwakarta Amanah Sejahtera (PAS) - Putranto Sigit; Ahmad Saepudin; Saepul Bahri; Yulia Purnama (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
Murabaah payments can be made in cash and installments. However, often in the installment process, banks are faced with various problems, especially bad loans. The problem that often occurs in banking is customers who are able but deliberately delay their obligations to the bank. This has resulted in the possibility of the bank experiencing material and non-material losses. in sharia banks in accordance with the DSN-MUI fatwa No. 17 of 2000, if the customer intentionally delays payment for no apparent reason, the sharia financial institution has the right to impose a fine on him in accordance with the previously agreed upon agreement. The purpose of this study was to determine the system of fines on sharia financing products at BMT PAS and to determine the implementation of fines on murabahah contracts in a sharia economic perspective at BMT Purwakarta Amanah Sejahtera (PAS). This type of research is field research, the data is obtained in the field, meaning that it is direct research to obtain data from the facts that occur on the BMT PAS with a qualitative descriptive approach. The data collection technique is done by triangulation (combined), data analysis is a deductive method, namely a method that departs from general knowledge about a phenomenon (theory) and is based on general knowledge that wants to assess specific things. The results of this study indicate that the penalty system for sharia financing products at BMT PAS is by giving policies to members affected by fource majeur by freeing them to pay their financing installments. If it is found that the economic condition of the member is able to pay the debt but does not obey the installments, then the BMT PAS will impose sanctions on the member. If the analyzed member is really economically incapable, then the BMT PAS does not impose a fine or sanction on the member. The Penalty System for Sharia Financing Products at BMT PAS is in accordance with fatwa No. 17/DSN-MUI/IX/2000 concerning Sanctions for Able Customers Who Delay Payments. Because BMT PAS considers Fource majeur to be a disaster, BMT PAS will provide a solution to the member by being retrained if it cannot be fostered, then BMT PAS releases members from paying the installments and is considered to be a loss from BMT PAS. Likewise, the BMT PAS has applied fines to members who can afford it but delay payments. Sanctions in the form of fines are based on the principle of ta'zir, which aims to make customers more disciplined in carrying out their obligations. in allocating the BMT PAS fines, it also clarifies that the fines are used for social funds or community needs, both for compensation, disaster relief infrastructure and so on